BANKRUPTCY OF LEGAL ENTITIES: PROCEDURES, LEGAL ISSUES, AND REFORM PROPOSALS - Tleumuratov Mambetbay Bazarbayevich; Adilbaeva Zulfiya Axmetovna; Rzambetov Salamat Rustamovich (Bright Mind Publishing, 2025)
This article explores the legal framework and procedural aspects of bankruptcy of legal entities in Uzbekistan. It investigates the national legislation, judicial practice, challenges in the enforcement of bankruptcy norms, and comparative experience from foreign jurisdictions. The research emphasizes the importance of transparency, creditor protection, and institutional efficiency in managing insolvency processes. The paper also proposes several reforms aimed at improving the effectiveness of bankruptcy regulation and aligning it with international standards.
Keywords: Bankruptcy, insolvency, legal regulation, Uzbekistan, economic court, liquidation, creditor protection, legal entities.